(3JaSjQ CHjGJ GdeYGfi ef TYQ GdeJfHis - (3SdjeGf Hf Ydj Hf eMeO Hf YHO Gddg Hf SdjeGf GdeYQis; (3GdeJfHj , CHh GdWjH,J (B354 (3g` s
(3ChdgG (B:s
(3CeG HYO (B: (3aEfg MVQ YfOi LeGYI ef Cgd GdCOH hSCda efge ef ChLH Mbg hChKQ ehGabJg LeY eG GfJgi Edi Ydeg ef CbhGd eaSQi OjhGf GdePchQ (B((3CHi GdWjH GdeJfHi (B) (3Ydi SHjd GdEjLGR hGdGNJUGQ s
(3BNQgG (B:s
(3SGY ai CdGQV hEfeG eSGYjc ai GdSeGA fLR GdeNJUQ ai JaSjQ CHjGJ GdeYGfi ef TYQ CHj GdWjH CMeO Hf GdMSjf GdeJfHi s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3JaSjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B115 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B201s
Keywords: (3GdCOHs